Prediction models of site index in Pinus ponderosa Dougl. from soil features, west andinopatagonia, 37°-41° S, República Argentina - Broquen, Patricia; Girardin, Jorge Luis; Falbo, Gabriel; Álvarez, Omar (Bosque (Valdivia), 1998)
This paper analyses the representative site characteristics of afforestations with Pinus ponderosa Dougl. in NeuquénArgentina. A multiple regression analysis between site factors and site index was done to obtain measurable parameters to estimate forest site quality. The site factors considered were: climatic, topographic and soil characteristics. The variables were selected considering the diagnostic importance of their characteristics, particularly those of volcanic ash soils. Among all the variables analysed, those with a significance level of 5% were the soil factors effective soil depth, organic matter, water at the end of the dry season related to permanent wilting point. Soil depth was the variable with the greatest significance.